The Influence of Emotional and Spiritual Intelligence on Work Loyalty and Teacher Performance - Achmad Mohyi; Nazaruddin Malik (Asia Pacific Journal of Management and Education (APJME), 2025)
Emotional and spiritual intelligence possessed by an employee, along with loyalty to their job and organization, are essential factors in maintaining and improving performance. This study aims to analyze the influence of emotional intelligence, spiritual intelligence, and work loyalty on teacher performance, and to examine the mediating role of work loyalty in the relationship between emotional and spiritual intelligence and performance. The study involved 100 Muhammadiyah School teachers in Malang, selected using proportional stratified random sampling. Data were collected through questionnaires and analyzed using the SEM-PLS method via SmartPLS software. The findings show that emotional intelligence significantly affects work loyalty (? = 0.587, t = 5.468, p = 0.000), as does spiritual intelligence (? = 0.306, t = 2.656, p = 0.008). Emotional intelligence (? = 0.202, t = 2.094, p = 0.036), spiritual intelligence (? = 0.330, t = 2.582, p = 0.010), and work loyalty (? = 0.407, t = 3.555, p = 0.000) all significantly affect performance. Work loyalty mediates the effect of emotional intelligence on performance (VAF = 54.20%) and the effect of spiritual intelligence on performance (VAF = 27.31%), both categorized as partial mediation. These findings highlight the critical role of emotional and spiritual intelligence and loyalty in enhancing teacher performance.